Interventions for the Prophylaxis and Treatment of Viral, Fungal, and Bacterial Infections in Patients Undergoing Allogeneic Hematologic Stem Cell Transplant. - Wolfe, Dianna; Yazdi, Fatemeh; Hutton, Brian; Moher, David; Bredeson, Chris; Cowan, Juthaporn; Allan, David (Université d'Ottawa | University of Ottawa, 2016)
OVERVIEW While hematologic stem cell transplant (HSCT) has become a vital therapy in treating patients with a variety of malignant and non-malignant disorders, a challenge that remains is the sizeable risk of mortality related to infection. Although advances in antimicrobial therapies in HSCT have occurred in recent years, infection still accounts for 16–19% of deaths after allogeneic HSCT. Considerable variability exists between treatment facilities regarding the care of HSCT patients with respect to infection prevention and treatment. This systematic review was performed to provide evidence to guide best practice development around this area of HSCT patient care. Objectives Addressed in this Review 1) To compare the benefits and harms of competing preventive (includes pre-emptive strategies) and treatment (includes pre-emptive/treatment) agents for viral infections in patients undergoing HSCT to establish a hierarchy of intervention strategies based on their efficacy and safety. 2) To compare the benefits and harms of competing preventive (includes pre-emptive strategies) and treatment (includes pre-emptive/treatment) agents for fungal infections in patients undergoing HSCT to establish a hierarchy of intervention strategies based on their efficacy and safety. 3) To compare the benefits and harms of competing preventive (includes pre-emptive strategies) and treatment (includes pre-emptive/empiric treatment) agents for bacterial infections in patients undergoing HSCT to establish a hierarchy of intervention strategies based on their efficacy and safety. METHODS The databases Medline, PubMed, Embase, and the Cochrane Register of Controlled Trials were searched for RCTs of patients undergoing HSCT. Studies were included if patients underwent allogeneic HSCT in the treatment of hematologic neoplasias or benign disease, and were randomly allocated to receive a pharmacological intervention for the prophylaxis or treatment of viral, fungal, or bacterial infections. Outcomes of interest included risk of disease (prophylaxis objectives), risk of infection (prophylaxis and pre-emptive treatment objectives), treatment success (treatment objectives), risk of drug-related neutropenia (viral prophylaxis), overall mortality, and non-relapse mortality. Within each objective (i.e., viral, fungal, and bacterial), we conducted separate analyses for prophylaxis, pre-emptive treatment, and treatment, using Bayesian network meta-analysis to compare interventions for outcomes of interest, where feasible. Where necessary, analyses were further subdivided by infectious organism (e.g., cytomegalovirus (CMV), herpes simplex virus (HSV), and varicella zoster virus (VZV) within the viral prophylaxis objective). All outcomes were analysed as binary endpoints, with summary comparisons between regimens reported as odds ratios with 95% credible intervals. For outcomes for which network meta-analyses were not possible, detailed narrative summaries have been provided. RESULTS Thirty-three trials assessed viral, fungal, and bacterial prophylaxis and treatment in a total of 7,712 patients. The interventions studied, numbers of trials, and numbers of patients have been summarized by review objective in Table 1. Overall, there was substantial variability in patient populations with respect to age, underlying hematologic disease, graft source, HLA matching of donor, and presence of graft-versus-host disease (GVHD). Trial publication dates ranged from 1985–2015. Interventions compared in included trials of viral, fungal, and bacterial prophylaxis and treatment Viral prophylaxis (13 trials; n = 2,682): • Acyclovir • Brincidofovir • Ganciclovir • Letermovir • Maribavir • Valaciclovir • Placebo Viral pre-emptive treatment (2 trials; n=285): • Foscarnet • Ganciclovir • Placebo Fungal prophylaxis (12 trials; n=3758): • Amphotericin B • Fluconazole • Itraconazole • Ketoconazole • Micafungin • Nystatin • Posaconazole • Voriconazole Fungal treatment (2 trials; n=153) • Amphotericin B • Voriconazole • Voriconazole + anidulafungin Bacterial prophylaxis (1 trial; n=155) • Vancomycin-added prophylaxis • No-vancomycin-added prophylaxis Bacterial empiric treatment (3 trials (n=679): • Cefepime • Ceftazidime • Meropenem • Netilmicin + imipenemin-cilastatin • Netilmicin + ceftazidime • Piperacillin + tazobactam __________________________________________________________________________ Objective 1: Comparing interventions for viral prophylaxis and pre-emptive treatment The included viral prophylaxis studies evaluated prevention of CMV (prophylaxis starting at engraftment: 9 trials; prophylaxis of late CMV in high-CMV-risk patients: 1 trial; pre-emptive treatment: 2 trials), HSV (prophylaxis: 2 trials), and VZV (prophylaxis: 1 trial). Network meta-analysis was only possible for outcomes reported in trials of CMV prophylaxis starting at engraftment. The ideal outcome to assess CMV prophylaxis (i.e., risk of confirmed CMV disease at 100 days post-transplant) was unavailable for many trials. Although most trials reported confirmed CMV disease during extended follow-up, after discontinuation of study drugs, these follow-up times varied substantially. In all networks, most comparisons were informed only by indirect evidence (i.e. head-to-head trials were not available), and many of the direct comparisons were based on single studies with small numbers of patients. This sparse evidence base reduced the robustness of NMAs. Viral prophylaxis objectives that could not undergo NMA were summarized narratively. Clinical interpretation of findings from NMAs and narrative summaries are as follows: Prevention of CMV disease using CMV prophylaxis starting at time of initial hematopoietic engraftment: Two NMAs were performed on endpoints measuring confirmed CMV disease during study treatment and over extended follow-up. Six interventions were included in the networks: ganciclovir, valaciclovir, acyclovir, brincidofovir, maribavir, and placebo. Few significant differences in prophylactics were found due to sparse evidence. Ganciclovir consistently trended to be the highest ranked intervention in both networks; however, ganciclovir was not significantly more efficacious than valaciclovir, acyclovir, or brincidofovir. Ganciclovir was significantly more efficacious than maribavir and placebo. • Impact on overall mortality using CMV prophylaxis starting at time of initial engraftment: Two NMAs measuring overall mortality at 100 and 180 days post-transplant were performed, including seven different interventions: ganciclovir (both networks), valaciclovir (180 days), acyclovir (180 days), maribavir (both networks), letermovir (100 days), brincidofovir (100 days), and placebo (both networks). No significant differences in prophylactics were found in either NMA. Only one small trial reported overall mortality at both 100 and 180 days post-transplant, highlighting the lack of consistency on reporting of outcomes in CMV prevention studies. Drug-related neutropenia in comparisons of CMV prophylaxis starting at engraftment: While ganciclovir may be most beneficial in the prevention of CMV disease, it was associated with a significantly higher risk of drug-related neutropenia than all other CMV prophylactic drugs in our NMA, which included valaciclovir, acyclovir, maribavir, and placebo. • Prevention of late CMV disease or infection (>100 days post-transplant) in high-CMV-risk patients: A single study compared valganciclovir with placebo in the prevention of late CMV disease beyond 100 days post-transplant in high-CMV-risk patients. The study design allowed comparison of prophylactic valganciclovir with PCR-guided pre-emptive treatment after 100 days post-transplant. No significant differences were found between prophylactic and pre-emptive treatment, with respect to confirmed CMV disease, mortality, or neutropenia. However, prophylactic valganciclovir was associated with a lower risk of CMV viremia while patients were on the study drug. No other drugs have been tested in RCTs. • Pre-emptive treatment of CMV infection: Two trials evaluating pre-emptive treatment of CMV were identified and summarized narratively. Ganciclovir was found to significantly reduce the risk of confirmed CMV disease, CMV pneumonia, and overall mortality at 180 days post-transplant compared to placebo, but not compared to foscarnet. At 100 days post-transplant, there was no difference in overall mortality between ganciclovir and placebo; however, non-relapse mortality was significantly reduced by ganciclovir. • Prevention of confirmed HSV disease: A pairwise meta-analysis was possible for two older studies published in 1987 and 1989 that compared acyclovir to placebo in the prophylaxis of HSV infection. When pooled, acyclovir was associated with a significantly reduced risk of HSV infection. • Prevention of confirmed VZV disease: A single study published in 1989 compared acyclovir to placebo in the prevention of VZV disease. While on study drugs to one year post-transplant, there was a significant reduction in the risk of confirmed VZV disease in acyclovir patients; however, the difference was not significant once study drugs were discontinued. • Key clinical messages regarding interventions for viral prophylaxis were as follows: o Based on limited evidence, ganciclovir trends to be the most effective antiviral agent to prevent confirmed CMV disease and CMV infection; however, it is associated with significant drug-related neutropenia. It is unclear if other antiviral agents (e.g., valaciclovir, acyclovir, and brincidofovir) may be equally efficacious and yet be associated with lower drug-related neutropenia. When used pre-emptively to treat CMV infection, ganciclovir performed significantly better than placebo in one study; however, it is unclear if other antiviral agents (e.g., foscarnet) may be equally efficacious. o All studies evaluating antivirals for HSV and VZV prophylaxis were published >25 years ago. In those studies, acyclovir significantly reduced the risk of both HSV and VZV infection, while patients were on medication. Objective 2: Comparing interventions for fungal prophylaxis and treatment Network meta-analysis was only possible for outcomes reported in trials evaluating fungal prophylaxis. Where NMAs were conducted, most comparisons were informed only by indirect evidence (i.e. head-to-head trials were not available), and many of the direct comparisons were based on single studies with small numbers of patients. This sparse evidence base reduced the robustness of NMAs. Trials evaluating treatment of fungal infections were summarized narratively. Primary findings from included studies were as follows: • Prevention of invasive fungal infections at any follow-up time: Three NMAs were conducted for (1) proven invasive fungal infections (IFIs), (2) proven or probable IFIs, and (3) any IFI (proven, probable, or possible). Five interventions were included: fluconazole (networks 1, 2, and 3), itraconazole (networks 1, 2, and 3), voriconazole (networks 1, 2, and 3), amphotericin B (networks 1 and 2), and micafungin (network 3 only). No significant differences were demonstrated between any of the fungal prophylaxis agents in networks evaluating proven IFIs or any IFI. Voriconazole was significantly more efficacious than fluconazole in the prevention of proven or probable IFIs; however, this finding should be interpreted cautiously due to limited evidence in the network. • Effects of fungal prophylaxis on overall and non-relapse mortality: One NMA was conducted evaluating overall mortality at 180 days and no significant differences were found amongst the three fungal prophylactics included (voriconazole, fluconazole, itraconazole). However, in a single-study narrative summary, ketoconazole demonstrated significantly reduced overall mortality compared to nystatin within 1 month of engraftment. Similarly, in narrative summaries, itraconazole and fluconazole were not significantly different with respect to non-relapse mortality at 180 or 250 days post-transplant. • Prevention of invasive fungal infections in GVHD patients: Two studies examined fungal prophylaxis starting at the time of GVHD diagnosis. Posaconazole was associated with significantly fewer proven or probable IFIs than fluconazole while patients were on study medication and up to 168 days after the diagnosis of GVHD. Voriconazole and itraconazole appeared equally efficacious at preventing proven and probable IFIs. No significant differences were demonstrated, however, between any of the antifungals with respect to overall mortality in patients with GVHD. • Treatment of aspergillosis: One study demonstrated that voriconazole was significantly more efficacious than amphotericin B in the treatment of aspergillosis, and that voriconazole reduced overall mortality at 12 weeks. Another study demonstrated that there were no significant differences between voriconazole alone and in combination with anidulafungin in either efficacy or overall mortality. Key clinical messages regarding interventions for fungal prophylaxis and treatment: o Based on limited evidence, voriconazole trends to be more efficacious than itraconazole, amphotericin B, and fluconazole in preventing IFIs after HSCT; however, these findings should be interpreted cautiously. No study evaluated posaconazole immediately after transplant and only three studies compared micafungin with triazole agents. None of these three trials reported data for the preferred more specific outcomes (“proven” and “proven or probable” IFIs). o Based on one study, posaconazole appears to be significantly more efficacious than fluconazole in preventing IFIs at the time HSCT patients are diagnosed with GVHD. o Based on one study, voriconazole appears more efficacious than amphotericin B in the treatment of aspergillosis in HSCT recipients. Objective 3: Comparing interventions for bacterial prophylaxis and treatment Network meta-analyses were not possible and narrative summaries were performed for bacterial prophylaxis and empiric treatment. • Bacterial prophylaxis: One study assessed the inclusion of vancomycin or not in bacterial prophylaxis regimens. Regimens that included vancomycin were not demonstrated to have significantly improved efficacy for preventing documented Gram-positive cocci infections, septicemia, or fever of unknown origin compared to regimens that did not include vancomycin. • Empiric treatment of febrile neutropenia: Febrile neutropenia was considered a proxy for bacterial infection. Three studies evaluated the treatment of febrile neutropenia in immunocompromised patients, including HSCT recipients, comparing (1) netilmicin + imipenem-cilastatin with netilmicin + ceftazidime, (2) meropenem with ceftazidime, and (3) piperacillin-tazobactam with cefepime. No significant differences were demonstrated between the netilmicin regimens in the improvement of febrile neutropenia. Meropenem was associated with significantly higher clinical success at the end of therapy than ceftazidime. Piperacillin-tazobactam was associated with significantly greater treatment success at 72 hours after the start of therapy compared to cefepime; however, this difference was not significant at later follow-up times. There were no differences in overall mortality between any of the interventions. • Key clinical messages regarding interventions for bacterial prophylaxis and empiric treatment: o There is a significant lack of data regarding antibacterial prophylaxis and empiric treatment of febrile neutropenia in HSCT recipients. o Studies evaluating the treatment of febrile neutropenia focused on antipseudomonal agents such as ceftazidime, cefepime, piperacillin-tazobactam, and meropenem. A trend toward better outcomes was suggested in the beta-lactam/beta-lactamase or carbapenem over antipseudomonal cephalosporins. RECOMMENDATIONS AND FUTURE STUDIES • Hematopoietic stem cell transplant recipients are at high risk of life-threatening viral, fungal, and bacterial infections post-transplant due to being severely immune-compromised. Numerous prophylactic, pre-emptive, and empiric treatments are available to reduce the risk of infection, disease, and death; however, some of these agents are associated with significant side-effects. This systematic review of the evidence, incorporating network meta-analyses where possible, was conducted to compare the benefits and harms associated with infectious disease interventions for HSCT recipients. Overall, thirty-three trials were included in the review, encompassing viral, fungal, and bacterial prophylaxis, pre-emptive, and empiric treatment. • We saw consistently across infection domains that there was limited evidence evaluating anti-infection agents in the HSCT population. As well, our NMAs consistently were unable to identify statistically significant differences between interventions for all types of infection prophylaxis and treatment, likely due to this paucity of evidence. We speculate that HSCT clinicians borrow evidence from other populations in their development of clinical strategies for infection control in HSCT patients. The following key points for clinical practice were identified in this review: • Ganciclovir is currently the most efficacious antiviral for CMV prophylaxis; however, it is associated with significant neutropenia compared to other anti-CMV agents. Newer yet equally efficacious antiviral medications or other novel approaches such as CMV vaccination or host-directed immune therapy are needed. • Voriconazole appears to be better than itraconazole, amphotericin B, and fluconazole in preventing IFI; however, studies evaluating posaconazole and echinocandins were lacking. Clear recommendations regarding fungal prophylaxis in HSCT recipients cannot be made. • There is a significant lack of data regarding bacterial prophylaxis and empiric treatment of febrile neutropenia in the HSCT setting. Clear recommendations in these areas cannot be made. At the design stage, future studies of infectious disease interventions for HSCT recipients should carefully consider the comparator of interest, the patient population, and assessment of the economics of the interventions. For example, pre-emptive treatment with ganciclovir remains the standard to which other antiviral strategies should be compared in the future. Similarly, voriconazole should be considered for comparison of other antifungals. The use of antifungal agents in HSCT recipients continues to be extrapolated from other immunocompromised populations and more transplant-focussed studies are recommended. Cost effectiveness should be assessed, given the significant cost of these drugs.
Keywords: Hematopoietic stem cell transplantation (HSCT); Peripheral blood; Allogeneic; Autologous; Infection; Graft-versus-host disease (GVHD); Prophylaxix; Treatment; Fungal; Bacterial; Viral